2018
DOI: 10.1016/j.prnil.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Status of TMPRSS2–ERG fusion in prostate cancer patients from India: correlation with clinico-pathological details and TMPRSS2 Met160Val polymorphism

Abstract: BackgroundProstate cancer (PCa) shows considerable clinical heterogeneity that has been primarily attributed to variable molecular alterations. TMPRSS2–ERG fusion is one such molecular subtype that has been associated with predominantly poor prognosis. More recently, a single nucleotide polymorphism (SNP) in the TMPRSS2 gene rs12329760 C>T (Met160Val) has been shown to positively correlate with the fusion status and also to be associated with increased risk for PCa. The aim of the present study is to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(53 reference statements)
0
20
0
Order By: Relevance
“…Besides, another study performed on 214 patients affected by prostate cancer showed that the T allele of rs12329760 was related to TMPRSS2-ERG fusion and prostate cancer pathogenesis (FitzGerald et al, 2008). These findings suggest that the high frequency of SARS-CoV2 infection in Chinese population may probably be due partly to their SNPs profile (Anonymous, 2020b;Pant et al, 2020). SNPs were analyzed by HSF in order to prediction of their effects on splice site.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Besides, another study performed on 214 patients affected by prostate cancer showed that the T allele of rs12329760 was related to TMPRSS2-ERG fusion and prostate cancer pathogenesis (FitzGerald et al, 2008). These findings suggest that the high frequency of SARS-CoV2 infection in Chinese population may probably be due partly to their SNPs profile (Anonymous, 2020b;Pant et al, 2020). SNPs were analyzed by HSF in order to prediction of their effects on splice site.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, growing body of evidence indicated the fundamental role of epigenetic mechanisms in regulating miRNA expression, and thereby development of several diseases including Alzheimer, and especially some types of carcinomas (breast, and colorectal) (Frick et al, 2019; Villela et al, 2016; Wu et al, 2019). Obtained results from PolymiRTS and miRSNPs revealed the vital role of miRNAs profile in regulation of TMPRSS2 expression, and thereby highlighted its possible effect on higher susceptibility of Asian populations especially Chinese (57 cases per million) and Iran in the middle East (873 cases per million), and European populations especially Spain (3625cases per million) to SARS-CoV2 (Anonymous, 2020a). Consequently, the present study emphasized on crucial role of SNPs throughout TMPRSS2 in individuals'susceptibility to SARS-CoV-2 infection via influencing several essential processes such as splicing, miRNA expression, epigenetic mechanisms, PTM, protein structure and gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Infection of the human cells with viral particles occurs through the binding of S viral 4 proteins to the receptors of the host cell and their subsequent priming with proteases. 5 ACE2 is considered the classic receptor for SARS-CoV-2, but there is evidence that it 6 can also use the BSG receptor (CD147) [33]. The priming of viral proteins is carried out 7 by the TMPRSS2 protease.…”
Section: Introductionmentioning
confidence: 99%